ChemInform Abstract: N‐(Diazoacetyl)oxazolidin‐2‐thiones as Sulfur—Donor Reagents: Asymmetric Synthesis of Thiiranes from Aldehydes. Issue 12 (14th March 2013) - Cano, Israel; Gomez‐Bengoa, Enrique; Landa, Aitor; Maestro, Miguel; Mielgo, Antonia; Olaizola, Iurre; Oiarbide, Mikel; Palomo, Claudio
Abstract The ability of the oxazolidin‐2‐thione group to act as an intramolecular sulfur donor and a stereodirecting group allows the synthesis of optically active thiiranes from substrates (I), (IX) and (XI) and aldehydes.